Nutritional Strategies for Maintaining Optimal Hemoglobin Levels in Soccer Players: A Review of Health Implications - Indra Adi Budiman; Yovhandra Ockta (Postgraduate, University of Mataram, 2024)
This study uses a literature review-based qualitative descriptive research model to explore nutritional strategies in maintaining optimal hemoglobin levels in football players. The research process begins with the collection of literature from reliable sources, by accessing scientific databases such as Scopus, Science Direct, and Google Scholar using keywords such as